The practice of silviculture : applied forest ecology - Ashton, Mark S. (Wiley, 2018)
The tenth edition of the classic work, The Practice of Silviculture: Applied Forest Ecology, includes the most current information and the results of research on the many issues that are relevant to forests and forestry. The text covers such timely topics as biofuels and intensive timber production, ecosystem and landscape scale management of public lands, ecosystem services, surface drinking water supplies, urban and community greenspace, forest carbon, fire and climate, and much more.